Improving the Marketing Performance of SMEs in Kudus Regency - Marka, Mira Meilia (Review of Management and Entrepreneurship, 2021)
This study used descriptive statistical methods. The goal to be achieved is to analyze the influence of social capital and human capital on marketing performance.The research sample of 201 respondents with SMEs in Kudus.The results showed that social capital has no significant effect on marketing performance and human capital has a positive and significant influence on marketing performance.